144=-2-6(6)6(10)

Simple and best practice solution for 144=-2-6(6)6(10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 144=-2-6(6)6(10) equation:


Simplifying
144 = -2 + -6(6) * 6(10)

Multiply -6 * 6
144 = -2 + -36 * 6 * 10

Multiply -36 * 6
144 = -2 + -216 * 10

Multiply -216 * 10
144 = -2 + -2160

Combine like terms: -2 + -2160 = -2162
144 = -2162

Solving
144 = -2162

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8t-2=33+t | | 2k+2=-1313k | | 4K=-9k | | 144=-2-6(6+10) | | 130=3x+2y | | 5x+1+4=11+9x | | 3m+2m+4n+3n= | | 9/4x=1/16 | | 2/3x=140 | | 1=12x-8 | | 5x+8=6x-18 | | 10/9c=-81 | | P-3.2=7.6 | | 7.3y-5.8=51.9 | | 53-2x=5x-17 | | 15+9n=9-n | | 2(7x+2)=-12 | | 2/3z=1/21 | | 50=5ln(3x+7) | | 84=2*35+2*w | | X(8-1)=18 | | -1=2x-8 | | -x/4-5=-8 | | -15+t=20 | | 4/3m=8/15 | | a/3-7=10 | | 25x+2000=2000 | | -7(2-6x)-4x=23+x | | -2+3=-(x+6) | | 84+36=93 | | 3*x+sqrt(3)=3*sqrt(3) | | 1/10=1/5y |

Equations solver categories